Assessing Thai entrepreneur performance : Steps toward a new venture production function / Chris Batstone, Geoff Perry and Pussadee Polsaram - Batstone, Chris; Perry, Geoff; Polsaram, Pussadee (Universiti Teknologi MARA Cawangan Pahang, 2005)
This paper describes the development and estimation of a New Venture Production Function (NVPF). It focuses on technical aspects of a project undertaken as a research collaboration between business economists and educators from the Auckland University of Technology(AUT) and The University of the Thai Chamber of Commerce (UTCC) investigating the attributes of successful Thai SME entrepreneurs in post currency crisis Thailand .The motivation for the innovation described in the paper is the questionable reliability of performance data collected by survey questions probing performance in a population of entrepreneurs. The NVPF is configured as a simple Cobb-Douglas specification estimated in first differences. The model estimation is based in a convenience sub-sample of 75 new venture entreneurs taken from a total sample of 537 Thai SME entrepreneurs surveyed by UTCC graduate students in October 2000. Hypothesis testing shows that the relationships predicted by theory between annual changes to new venture output and financial and human capital are evident in this population of entrepreneurs. This analytic convenience enables analysis of survey questions couched terms of percentage change of sales. This measure of Thai SME performance is designed to circumvent potential weaknesses in data provided by survey respondents.